Entre pais e filhos: reflexões teóricas e ressonâncias atuais da psicanálise com crianças - Barcessat, Belizia Aben-Athar (2010)
Focused in psychoanalytic references, this research faces the comprehension of some subjective and cultural processes, which concern the establishment of parental connections with the child. Theory-context-based and resulting from experiences in clinical work, this investigation intends to identify the aspects that characterize the way in which each parent personifies and sustains the primary functions in enabling a child s humanization and individualization, and in grounding the effectiveness of a child s enrolment in a social group. The developed analyses were caused by psychoanalytic experience with children and by the interest in theory and in clinical practice around the questions that involve the functioning of children s psychic and social life. Therefore, the considerations in this dissertation focus more specifically in the fatherly component of parental ties. This approach is associated with recognition conditions that surround fatherhood, when a subject takes over this role towards the child, sustains the essential the affective links and represents a very important reference and support to the child s subjectivity s subsidence. The recognition question is also a central topic among the reflections that involve the child and its processes of individualization and adherence to social offer and relationship. The articulations between the particularity of the fatherhood s bond and the child s subjective position are developed from the swapping between theoretical and clinic readings, published in the specialized literature, and confronted with the interpretations alignment and the clinical experience of the author in the field of children psychoanalysis. In this overview, becomes evident the narrow confluence of the psychic determinants and those determinants related to the social shifting plane, aggregated in modern recent history - shifts that include, significantly, the role and the model of the father figure